An Investigation of the Low Beta Anomaly on the JSE - Wright, Tarryn (My University, 2016)
This study aims to investigate the presence of the low market risk (beta) anomaly in the Johannesburg Stock Market (JSE). Finance theory suggests that with higher return comes higher risk. However, several studies have reported evidence of low risk anomaly in global markets where portfolios containing low beta shares delivers superior risk adjusted returns compared to market index and high beta shares' portfolio. This study will explore various risk return relationships on the JSE and test a variety of potential explanations of the anomalous behaviour of the low beta premium. Three explanations have been identified as potential factors that contribute to the persistence of the Low Beta Anomaly. These include; Net International Equity flows (NIEF), Idiosyncratic Risk and Market Concentration. The results are consistent with international literature indicating a persistent Low Beta Anomaly on the JSE. However, the results also indicate that in periods of turmoil, high beta shares outperform low beta shares i.e. during the Global Financial Crisis. Although some significant relationships are found between the low minus high beta differential and NIEF. NIEF is unable to suitably explain the anomaly. Idiosyncratic risk results are mixed depending on the model used to calculate the idiosyncratic risk estimates. Despite being a significant issue on the JSE, Market concentration does not explain the Low Beta Anomaly. As the superior performance of the low beta portfolios remains once the portfolios returns have been adjusted for the different variables however magnitude ofthe outperformance ofthe low beta portfolio was to a lesser degree.
Thesis (M.Com. (Finance))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Economic and Business Sciences, 2016
Keywords: JSE; Low risk anomaly; Low beta shares